Deviation of Boron Concentration From Predictions Using Salinity in Coastal Environments. Issue 9 (7th May 2019) - Lee, Kitack; Lee, Chang‐Ho; Lee, Ju‐Hyeon; Han, In‐Seong; Kim, Miok
Abstract: To test whether the established B/Cl ratio (0.2414 mg·kg –1 ·‰ –1 ) derived for the open ocean is applicable to coastal systems globally, we measured the B concentration and salinity of seawater samples ( n = 245) collected from the coastal waters of the Yellow, East China, and East Seas. We also measured the B concentration of freshwater samples ( n = 10) from six rivers discharging into these seas and analyzed along with the B concentrations of other rivers globally, obtained from literatures. Our results show that the supply of riverine B (2–6 μmol B/kg) did not discernably alter the B/Cl ratio in most estuarine systems. The impact of this riverine B input on the interconversion between total alkalinity ([HCO3 – ] + 2[CO3 2– ] + [B (OH)4 – ] + others) and carbonate alkalinity ([HCO3 – ] + 2[CO3 2– ]) is less than a few micromoles per kilogram for most estuarine and coastal systems, although exceptions in the Baltic Sea do occur. Plain Language Summary: Accurate data on boron (B) concentration (mg/kg) are critical for seawater thermodynamic calculations, including the interconversion between total alkalinity ([HCO3 – ] + 2[CO3 2– ] + [B (OH)4 – ] + others) and carbonate alkalinity ([HCO3 – ] + 2[CO3 2– ]). These conversions are made using the dissociation constant of boric acid and the total B concentration, derived from chlorinity (Cl, in per mil (‰); calculated from salinity) and the ratio of B to Cl (derived from open ocean data). The established B/Cl ratio implicitly assumes a zero B concentration in river discharges entering coastal seas and thus does not reflect riverine B concentrations. The consistent ratio of B to Cl concentrations found in coastal waters of the Yellow, and East China, and East Seas provides compelling evidence that the poorly studied processes (e.g., ocean biology, atmospheric deposition, and river discharges) have nondetectable impacts on the ocean B concentration and thereby do not change the B/Cl ratio established for the open ocean environments. The low B concentration (mean of 3 μmol/kg) measured in all major rivers flowing into the East China, Yellow, and East Seas, along with the low degree of dilution in these areas, supports use of the B/Cl ratio of 0.2414 reported for the open ocean environments. Key Points: Variation in the B concentration from that based on the established B/Cl ratio is common to most coastal areas under riverine influence The impact of B concentration variation on the conversion of total alkalinity to carbonate alkalinity (or vice versa) is insignificant The supply of riverine B was not large enough to alter the B/Cl ratio in the coastal systems of the Yellow, East China, and East Seas